“As long as they behave themselves”: Heterosexual recuperation in South Africans’ talk about homosexuality - Morison, Tracy; Mtshengu, Amanda; Sandfort, Theodorus; Reddy, Vasu (PINS-Psychology in Society, 2024)
Several qualitative researchers using discursive methodologies have noted how opposition to homosexuality has not necessarily diminished, despite the general expression of liberal tolerance in many settings. Instead, heterosexist rhetoric has shifted to accommodate political change. Our research builds on this observation within the South African context, using a discursive psychology approach. We examine rhetorical strategies of “heterosexual recuperation”: the ways that heterosexual boundaries and the dominance of heterosexuality are maintained by speakers, at the same time as they attempt to avoid being heard as heterosexist. Drawing on data from a qualitative study conducted with heterosexual-identifying Black South Africans (32) from four provinces, we focus on talk that was resourced by a “discourse of tolerance” and characterised by speakers’ concern to avoid the attribution of heterosexism. This talk was analysed using thematic analysis, to which discursive psychology techniques were applied. We identified two ways of speaking that relied on this discourse – (1) “As long as they do it in private”, and (2) “Flashing their homosexuality” – and show how they ultimately worked to recuperate heterosexuality and marginalise non-normative sexualities. We discuss the implications of these findings in relation to a critical psychology that works to challenge hetero-patriarchal norms.